Deteksi Komentar Spam Bahasa Indonesia Pada Instagram Menggunakan Naive Bayes - Antonius Rachmat C; Yuan Lukito (Faculty of Engineering and Informatics, Universitas Multimedia Nusantara, 2017)
Instagram is the most famous pictures and videos media sharing based on the web & mobile application. Instagram users can have picture posts that can be commented by their followers. Indonesian public figures such as actors, actresses, musicians use Instagram to promote their activities to their followers. Unfortunately, there are a lot of spam comments in Instagram that need special attention and have to be removed. This research grabs Instagram comments and builds the dataset from Indonesian public figures who have more than one million followers. By using preprocessing (tokenization, stop words removal, and stemming), TF-IDF weighting, and supervised learning, Naive Bayes method is used to detect spam comments in Indonesian. Naive Bayes produces 74,31% accuracy rate on unbalanced datasets and 77,25% accuracy rate on balanced datasets. This result shows that Naïve Bayes can be used to build an automatic Indonesian spam comments detector on Instagram with high accuracy rate. The novelty of this research is that Naive Bayes can be used to detect spam comment on our Indonesian Instagram comments dataset. Index Terms—Instagram, Naive Bayes, Indonesian spam comments, spam comments detection.